PARENTAL RESPONSIBILITY AFTER DIVORCE: THE LAW OF KOSOVO IN A COMPARATIVE CONTEXT (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
Parental responsibility as a legal institution includes rights and obligations both parents have towards their children, including making decisions about their health, education, and overall welfare. This responsibility, inexorable among third parties, flows throughout the marriage or its annulment, after divorce, and during the factual relationship. The legal norms that regulate this institution are imperative, meaning that the subjects exercising parental rights cannot alter them by their own volition, transfer them to others, or inherit them, as they are of an "intuitu personae". This institution is of paramount importance because it safeguards the fundamental rights of children, always respecting the best interest of them and is valid until they reach the age of 18, and in exceptional cases even beyond this age.The aim of this paper is to help parents develop an understanding of parental responsibilityafter divorce,which faces many challenges that can affect the well-being of children and the relationship of parents,while always prioritising the best interests of the child. The most challenging questions that ex-spouses ask themselves are who will our children live with? What happens if we cannot agree on where the children will live and how often will I see our children? Effective communication between parents is crucial but can be challenging, especially after a divorce. Divorce can be difficult and causes trauma to the ex-spouse in terms of the division of parental responsibility, and challenges often arise as to who the common child will live with.
Keywords: parental responsibility, children, divorce, child custody